2020
DOI: 10.3389/fimmu.2020.00259
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Dendritic Epidermal T Cell (DETC) Research From 1983 to 2019

Abstract: Dendritic epidermal T cells (DETC) are a group of immune cells expressing canonical γδ TCR in the murine epidermis. Similar to γδ T cells in the human epidermis, DETC serve an important barrier cell in the skin and participate in skin immune surveillance, immune regulation, skin homeostasis, tissue protection, and other activities. Since its discovery in 1983, research on DETC has grown rapidly and unevenly. To evaluate DETC research trends and map the DETC knowledge structure, we have applied bibliometric met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 84 publications
(91 reference statements)
3
56
0
Order By: Relevance
“…And finally, we conducted the search with the following formula, designed according to the search rules of Scopus (Deng et al, 2020 ): TITLE-ABS-KEY (“human coronavirus” OR “human corona virus” OR HCoV OR “novel coronavirus” OR “novel corona virus” OR nCoV OR “severe acute respiratory syndrome” OR ({SARS} AND “ * CoV” OR * virus OR crisis OR outbreak OR epidemic OR pandemic) OR “SARSr-CoV” OR “middle east respiratory syndrome” OR ({MERS} AND “ * CoV” OR * virus OR crisis OR outbreak OR epidemic OR pandemic) OR “camel flu” OR “EMC/2012” OR “coronavirus disease 2019” OR “COVID-19” OR (coronavirus OR “corona virus” OR “ * CoV” AND 229E OR OC43 OR NL63 OR HKU1) OR HCoV229E OR HCoVOC43 OR HCoVNL63 OR HCoVHKU1) ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And finally, we conducted the search with the following formula, designed according to the search rules of Scopus (Deng et al, 2020 ): TITLE-ABS-KEY (“human coronavirus” OR “human corona virus” OR HCoV OR “novel coronavirus” OR “novel corona virus” OR nCoV OR “severe acute respiratory syndrome” OR ({SARS} AND “ * CoV” OR * virus OR crisis OR outbreak OR epidemic OR pandemic) OR “SARSr-CoV” OR “middle east respiratory syndrome” OR ({MERS} AND “ * CoV” OR * virus OR crisis OR outbreak OR epidemic OR pandemic) OR “camel flu” OR “EMC/2012” OR “coronavirus disease 2019” OR “COVID-19” OR (coronavirus OR “corona virus” OR “ * CoV” AND 229E OR OC43 OR NL63 OR HKU1) OR HCoV229E OR HCoVOC43 OR HCoVNL63 OR HCoVHKU1) ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly true in the current age, where thousands of reports can be easily exchanged between public health specialists and healthcare providers across the internet (Takahashi-Omoe and Omoe, 2012 ; Unkel et al, 2012 ). Bibliometrics is also recognized as an essential tool and is widely used in a variety of fields to measure and evaluate scientific research quantitatively and qualitatively (Aggarwal et al, 2016 ; Romero and Portillo-Salido, 2019 ; Deng et al, 2020 ). Therefore, in order to accurately, effectively and systematically reveal connections within the human coronavirus field, our study applied bibliometrics and visualization methods to analyze human coronaviruses-related publications and citations, countries and affiliations, as well as journal performance, author impact and keyword co-occurrence cluster.…”
Section: Introductionmentioning
confidence: 99%
“…To further determine whether the loss of Zdhhc2 will affect the functions of the three types of T cells, the transfer experiment was performed by intravenous injection of purified lymph node CD45.2 + T cells into CD45.1 + CD3ϵ −/− mice. However, previously studies showed that γδ T cells represent only 1~2% of all T cells in lymph nodes ( 26 ), and DETC are only restricted to the murine epidermis ( 27 ). Therefore, we mainly detected the absolute number of CD45.2 + total T cells and CD45.2 + αβ T cells in the inflamed skin ( Supplementary Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research revealed that BTN3A1 was required in the activation of human Vγ9Vδ2 T cells (15), and BTNL3 and BTNL8 were found to bind Vγ4 + TCR (16,17). In mice, Skint1, the new member of BTN family, was required for positive selection of Vγ5 + T cells in the embryonic thymus and contributed to normal levels of these dendritic epidermal T cells in skin, which play an important role in wound healing and preventing cancer (18,19). BTNL1 and BTNL6 jointly regulated intestinal Vγ7 γδ T-cell function in mice, and human gut epithelial cells expressed BTNL3 and BTNL8 and stimulated Vγ4 γδ T cells (17).…”
Section: Introductionmentioning
confidence: 99%